2017
DOI: 10.4103/2045-9912.215745
|View full text |Cite
|
Sign up to set email alerts
|

Case control study: Hyperbaric oxygen treatment of mild traumatic brain injury persistent post-concussion syndrome and post-traumatic stress disorder

Abstract: Mild traumatic brain injury (TBI) persistent post-concussion syndrome (PPCS) and post-traumatic stress disorder (PTSD) are epidemic in United States Iraq and Afghanistan War veterans. Treatment of the combined diagnoses is limited. The aim of this study is to assess safety, feasibility, and effectiveness of hyperbaric oxygen treatments (HBOT) for mild TBI PPCS and PTSD. Thirty military subjects aged 18–65 with PPCS with or without PTSD and from one or more blast-induced mild-moderate traumatic brain injuries t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(88 citation statements)
references
References 75 publications
8
78
2
Order By: Relevance
“…Specifically, critical information regarding the optimal therapeutic time frame of NBO and its long-term effects are still unclear Therefore, it does not serve the same effectiveness as the HBOT for post- and pre-stroke conditions and is less of an intriguing option for preconditioning [ 16 , 24 , 25 ]. Nevertheless, the synergistic use of normobaric oxygen treatment accompanied by HBOT shows promise in reducing stroke mortality [ 2 , 29 ]. Recent in vivo investigations have shown that HBOT and normobaric oxygen treatment may widen the limited window for thrombolytic therapy, and various neuroprotective medications [ 29 , 30 ].…”
Section: Hbot In Ischemic Stroke: Potential Benefits and Limitatiomentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, critical information regarding the optimal therapeutic time frame of NBO and its long-term effects are still unclear Therefore, it does not serve the same effectiveness as the HBOT for post- and pre-stroke conditions and is less of an intriguing option for preconditioning [ 16 , 24 , 25 ]. Nevertheless, the synergistic use of normobaric oxygen treatment accompanied by HBOT shows promise in reducing stroke mortality [ 2 , 29 ]. Recent in vivo investigations have shown that HBOT and normobaric oxygen treatment may widen the limited window for thrombolytic therapy, and various neuroprotective medications [ 29 , 30 ].…”
Section: Hbot In Ischemic Stroke: Potential Benefits and Limitatiomentioning
confidence: 99%
“…In light of the current COVID-19 pandemic, clinical trials have explored HBOT in infected patients experiencing extreme respiratory distress. COVID-19 infection generates a potent cytokine storm that spurs the onset of progressive hypoxia, leading to severe respiratory illness [ 2 , 87 ]. Furthermore, HBOT’s capacity to enhance oxygen flow and attenuate inflammation may bear curative effects in COVID-19 patients [ 87 ].…”
Section: Implications Of Hbot In Other Neurological and Non-neurolmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in a few small military cohorts of 45 service members with chronic blast-induced mild to moderate TBI, PPCS, and PTSD, forty 60-minute sessions of HBOT 1.5 ATA resulted in 36% to 96% increases in perceived quality of life and percentage back to normal cognitive, physical, and emotional function reported. 28,31 There are also many testimonials and anecdotal reports of HBOT as a "miracle cure" for TBI and/or PTSD that is "giving people back their lives." 32,33 Based on such anecdotal reports, HBOT has gained some political advocacy, such as from Congressman Walter B. Jones in North Carolina and other lawmakers, which has resulted in Oklahoma, Texas, and Indiana passing legislation establishing funding to provide eligible Veterans with TBI and/or PTSD with access to HBOT.…”
Section: Debate On Hbot For Tbi/ptsdmentioning
confidence: 99%